Electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite, preparation method and CIP detection method
By preparing zinc oxide/graphene oxide/polythiophene ternary nanocomposite modified electrodes, the problems of high cost, cumbersome sample pretreatment and long analysis time of ciprofloxacin residue detection in the prior art are solved, and a fast, efficient and sensitive detection effect is achieved.
Patent Information
- Application Number
- CN202510067081.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has problems such as high testing costs, cumbersome sample preprocessing, and long analysis time when detecting ciprofloxacin (CIP) residues. The sensitivity and accuracy of the bare glass carbon electrode are low, making it difficult to effectively detect contaminants.
Zinc oxide/graphene oxide/polythiophene ternary nanocomposite was prepared by ultrasonic method, and the glass carbon electrode was modified to form a zinc oxide/graphene oxide/polythiophene-based electrochemical sensor for detection of ciprofloxacin residues.
It improves electron transfer efficiency, enhances conductivity and electroactive surface area, and achieves fast, sensitive and efficient detection of ciprofloxacin, has low detection limits and good anti-interference ability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensors, and in particular relates to the preparation and application of an electrochemical sensor of a zinc oxide / graphene oxide / polythiophene-based ternary nanocomposite. Background Art
[0002] Ciprofloxacin (CIP) belongs to the third generation of fluoroquinolone antibiotics (FQs) and has been widely used due to its strong antibacterial effect. However, there are increasing reports on adverse reactions such as carcinogenicity, teratogenicity, and mutagenicity of CIP. At the same time, due to its long half-life and difficulty in removal, CIP residues are often detected in various waters, which poses a serious threat to human health and the ecological environment. In recent years, many analytical methods have been developed to detect the content of CIP in water environments, such as spectrophotometry, high performance liquid chromatography (HPLC), high performance liquid phase tandem mass spectrometry (HPLC-MS / MS), fluorescence analysis, capillary electrophoresis, and electrochemical methods. Although these instrumental analysis methods have good accuracy and sensitivity, they still have the following disadvantages: expensive testing costs, cumbersome sample pretreatment, and long analysis time. Therefore, it is necessary to develop a new analytical technology for rapid, efficient, and specific detection of CIP residues.
[0003] Compared with other analytical methods, electrochemical analysis technology has the advantages of simple equipment, easy operation, fast response time, easy miniaturization and portable design, as well as excellent selectivity and sensitivity. In the process of electrochemical detection, the performance of the electrode is crucial. Due to the complex matrix of environmental water samples and the presence of many interfering substances, the sensitivity and accuracy of the electrode will be affected. In addition, the high potential and low sensitivity of the bare glassy carbon electrode (GCE) limit its application in pollutant detection. Selecting a suitable nanocomposite modified electrode is an effective solution. Graphene oxide (GO) is a carbon nanomaterial with a two-dimensional structure. It has high chemical stability, large specific surface area, and excellent conductivity. In addition, due to the large number of oxygen-containing functional groups such as hydroxyl groups and epoxy groups on the surface of the structure, it is easy to modify the surface and combine it with different functional materials (such as metal nanoparticles, conductive polymers, metal oxides, etc.) to form a graphene-based composite. Through the synergistic effect between different materials, the selective enrichment of target substances can be improved in electrochemical detection, achieving a lower detection limit and good selectivity.
[0004] The present invention prepares a ternary nanocomposite of ZnO / GO / PTH by an ultrasonic method, which can not only effectively improve the electron transfer efficiency and enhance the conductivity, but also prevent GO from agglomerating by the addition of ZnO, greatly increasing the electroactive surface area during the oxidation process with the target to be measured. The polythiophene prepared by chemical oxidation polymerization uses ferric chloride as a p-dopant to form a hole conductive layer of PTH, thereby improving the conductivity and enhancing the current signal. The ZnO / GO / PTH ternary nanocomposite is fixed to the surface of a glassy carbon electrode by a drop coating method to obtain a zinc oxide / graphene oxide / polythiophene-based electrochemical sensor, which is successfully applied to the detection of ciprofloxacin residues in environmental water. Summary of the invention
[0005] In order to solve the shortcomings of the above-mentioned technology, the present invention provides a method for preparing an electrochemical sensor of a zinc oxide / graphene oxide / polythiophene ternary nanocomposite and a method for detecting CIP.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: preparation of an electrochemical sensor based on a ZnO / GO / PTH ternary nanocomposite, the preparation method comprising the following steps: (1) Preparation of nano zinc oxide (ZnO): prepare a certain concentration of zinc acetate dihydrate aqueous solution, add a certain concentration of sodium hydroxide solution until the solution is alkaline, and continue to stir the reaction. Wash the precipitated product with deionized water several times, freeze-dry, place it in a muffle furnace for calcination for several hours, and grind the obtained solid mortar to obtain nano zinc oxide particles. (2) Preparation of zinc oxide / graphene oxide / polythiophene ternary nanocomposite (ZnO / GO / PTH): first take a certain amount of nano zinc oxide particles prepared in step (1), use anhydrous ethanol as a solvent, prepare a uniformly dispersed suspension, add an appropriate amount of graphene oxide, and react with ultrasound for a certain time. Prepare polythiophene (PTH) by chemical oxidation polymerization, take a certain amount of the prepared PTH and add it to the above reaction solution, and continue to ultrasound. After the reaction is completed, the obtained solid is filtered, washed and dried to obtain the zinc oxide / graphene oxide / polythiophene ternary nanocomposite. (3) Preparation of zinc oxide / graphene oxide / polythiophene ternary nanocomposite modified electrode (ZnO / GO / PTH / GCE): A proper amount of zinc oxide / graphene oxide / polythiophene dispersion is drop-coated on the surface of the pretreated glassy carbon electrode (GCE) by drop coating and naturally dried to obtain the zinc oxide / graphene oxide / polythiophene ternary nanocomposite modified electrode ZnO / GO / PTH / GCE.
[0007] Furthermore, in step (1), the concentration of zinc acetate dihydrate is 0.1 mol / L, the volume is 100 mL, the concentration of sodium hydroxide is 0.5 mol / L, the pH is 8.0, the stirring reaction time is continued for 2 h, the freeze-drying time is 12 h, and the pyrolysis reaction conditions in the muffle furnace are calcined at 400 ° C for 2 h.
[0008] Furthermore, in step (2), the amount of nano zinc oxide, graphene oxide and polythiophene is 20 mg, the ultrasonic dispersion time of nano zinc oxide particles is 1 hour, graphene oxide and polythiophene are added in sequence, the ultrasonic time interval is 0.5 hour, and the drying conditions are: vacuum drying at 80 ° C for 12 hours.
[0009] Furthermore, in step (3), the volume of the zinc oxide / graphene oxide / polythiophene ternary nanocomposite dispersion is 8 μL, the concentration is 0.2 mg / mL; the volume fraction of acetic acid is 10%, and the amount of chitosan is 0.05 g.
[0010] The application of electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite was successfully applied to the detection of ciprofloxacin (CIP) content in environmental water. The application method of electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite, the detection method mainly includes the following steps: Ⅰ. Prepare 1.2 mmol / L ciprofloxacin standard solution and environmental water sample solution; Ⅱ. Use the prepared zinc oxide / graphene oxide / polythiophene ternary nanocomposite modified electrode as the working electrode, platinum sheet as the counter electrode, silver / silver chloride as the reference electrode, and use cyclic voltammetry, differential voltammetry and electrochemical impedance to study the electrochemical behavior of ciprofloxacin (CIP) on the modified electrode ZnO / GO / PTH / GCE. Ⅲ. Detect ciprofloxacin solutions of different concentrations by differential pulse voltammetry, record the relationship between the oxidation peak current value and its concentration, and establish a standard curve, and use the standard addition method to determine the environmental water sample and calculate the recovery rate.
[0011] Furthermore, in step I, the actual environmental water sample is diluted with a 0.05 mol / L PBS buffer solution with a pH of 7.0 at a volume ratio of 1:10 for later use.
[0012] Furthermore, in step II, the CV scan rate is 50 mV / s; the DPV amplitude is 0.05 V, and the potential increment is 0.004 V; the initial frequency Init E (V) of EIS is -0.23 V, the amplitude is 0.005 V, and the rest time is 2 s. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 SEM images of different nanocomposites of the present invention: zinc oxide (A), polythiophene (B), graphene oxide (C) and zinc oxide / graphene oxide / polythiophene (D), and an EDS spectrum of zinc oxide / graphene oxide / polythiophene (E).
[0014] Figure 2FTIR spectra (A) and XRD (B) of different nanomaterials of the present invention: zinc oxide, graphene oxide, polythiophene and zinc oxide / graphene oxide / polythiophene composite.
[0015] Figure 3 Cyclic voltammetry curves CV(A) and differential voltammetry curves DPV(B) of different working electrodes of the present invention: bare electrode, zinc oxide, graphene oxide, polythiophene and zinc oxide / graphene oxide / polythiophene composite modified electrode in a mixed solution of 1 mmol / L K3[Fe(CN)6] and 0.2 mol / L KNO3, as well as electrochemical impedance spectroscopy curves EIS(C) in a mixed solution of 5 mmol / L K3[Fe(CN)6] / K4[Fe(CN)6] and 0.1 mol / L KCl, and an equivalent circuit diagram is attached.
[0016] Figure 4 (A) DPV curves of zinc oxide / graphene oxide / polythiophene modified electrode under different concentrations of ciprofloxacin; (B) oxidation peak current I pa The relationship curve between the concentration of ciprofloxacin and the DETAILED DESCRIPTION
[0017] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. Example 1
[0018] Preparation of zinc oxide / graphene oxide / polythiophene-based electrochemical sensor, the specific preparation steps are as follows: (1) Take 100 mL of 0.1 mol / L zinc acetate dihydrate solution and stir continuously for 3 h. Then slowly add 0.5 mol / L NaOH solution to the above solution until the pH is 8.0. Continue stirring and react for 2 h, then centrifuge and wash with deionized water, freeze-dry for 12 h, calcine in a muffle furnace at 400 °C for 2 h, and grind with a mortar to obtain nano zinc oxide particles. (2) Add 20 mg of the prepared nano ZnO to 10 mL of anhydrous ethanol and form a suspension by ultrasonic treatment for 1 h. Then, transfer 20 mg of GO to the above suspension and then ultrasonicate for 0.5 h. Then add 20 mg of PTH to the suspension and continue ultrasonication for 0.5 h. Finally, after vacuum drying at 80 °C for 12 h, the ZnO / GO / PTH ternary nanocomposite is obtained. (3) Preparation of ZnO / GO / PTH ternary nanocomposite modified electrode: 2 mg of ZnO / GO / PTH complex was dispersed in a previously prepared acetic acid / chitosan (0.05 g chitosan and 10% acetic acid) mixed solution and ultrasonicated for 2 h to obtain a uniform suspension with a concentration of 0.2 mg / mL. 8 μL of the above dispersion was fixed on the surface of glassy carbon electrode (GCE) by drop coating and naturally dried at room temperature to obtain ZnO / GO / PTH ternary nanocomposite modified electrode (ZnO / GO / PTH / GCE). Example 2
[0019] like Figure 1 SEM images of several materials are described. Zinc oxide appears as high-density spherical agglomerates with uniform particle size, while the material structure of polythiophene appears as irregular spherical agglomerates with uneven particle size distribution. The SEM image of graphene oxide shows a blocky structure with a flat surface and dry boundaries. The structure of the ternary nanocomposite is rich in porosity and wrinkles, and very thin graphene-like nanosheets of about 2 to 3 layers can be clearly seen at the edge of graphene oxide. The interfacial interaction and mechanical interlocking between polythiophene and graphene oxide sheets increase the dispersibility of graphene oxide sheets and enhance the π-π interaction through the thiophene rings of the polythiophene structure, which is an important factor in improving the conductivity of the nanocomposite. Example 3
[0020] The ZnO / GO / PTH composite prepared in Example 1 was subjected to Fourier infrared spectroscopy and X-ray diffractometer analysis. Figure 2 As shown. 451 cm -1 It is the characteristic absorption peak of Zn-O bond. Graphene oxide (GO) is at 3432 cm -1 is the characteristic absorption peak of OH, 1625 cm -1The absorption peak is C=O, 1394 cm -1 The absorption peak is due to the deformation of OH, 1091 cm −1 The absorption peak is the CO in the ether group. Polythiophene (PTH) is at 1681 cm -1 is the symmetric stretching vibration of the C=C ring of the thiophene ring, 692 cm −1 The characteristic peak of the composite is the CS stretching peak. The composite concentrates the characteristic peaks of ZnO, GO and PTH, indicating that ZnO-GO-PTH was successfully prepared. In the XRD spectrum, GO has a clear diffraction peak at 2θ = 10.0°, PTH has a weaker diffraction peak at 2θ = 23.1°, and the zinc oxide diffraction peaks are at 2θ = 31.7°, 34.4°, 36.2°, 47.5°, 56.6°, 62.8°, 66.4° and 68.0°. The composite concentrates the diffraction peaks of ZnO, GO and PTH, all indicating that the composite was successfully prepared. Example 4
[0021] The electrochemical sensor was prepared by a three-electrode system with a ZnO / GO / PTH modified glassy carbon electrode as the working electrode, a platinum electrode as the counter electrode, and a saturated silver / silver chloride electrode as the reference electrode. The electrochemical behavior of the ZnO / GO / PTH-based electrochemical sensor prepared in Example 1 was characterized by cyclic voltammetry, differential pulse voltammetry, and impedance spectroscopy. Figure 3 As shown in A and B, the cyclic voltammetry (CV) and differential pulse voltammetry (DPV) curves of different working electrodes GCE, ZnO / GCE, GO / GCE, PTH / GCE, and ZnO / GO / PTH / GCE in a mixed solution of 1mmol / L K3[Fe(CN)6] and 0.2mol / LKNO3. Under ZnO / GCE, ΔE p There is almost no change. This indicates that the aggregation of ZnO nanoparticles on the GCE surface delays the rate of electron transfer. When graphene oxide modifies the bare GCE surface, its anodic peak and cathodic peak are significantly increased, indicating that graphene oxide has excellent conductivity. On the other hand, a pair of redox peaks with strong current response are also obtained under PTH / GCE, which indicates that PTH nanoparticles can also effectively improve the electron transfer efficiency of the electrode. The ZnO / GO / PTH / GCE electrode has the largest current and the lowest potential. Figure 3 C is the electrochemical impedance spectroscopy (EIS) curves (EIS) of different working electrodes measured in 5mmol / L K3[Fe(CN)6] / K4[Fe(CN)6] in 0.1mol / L KCl solution expressed as Nyquist plot. ct The value is about 911 Ω. For ZnO / GO / PTH / GCE electrode, R ctThe semicircle of the frequency decreases to 295 Ω, which is the GCE R ct The value is one third of the value, indicating that electron transfer occurs on the surface of the modified electrode. This result is consistent with the results of the above cyclic voltammetry test (CV), indicating that the ZnO / GO / PTH composite has been successfully synthesized. Example 5
[0022] Under the optimal experimental conditions, the DPV curves of ciprofloxacin at different concentrations were measured using the zinc oxide / graphene oxide / polythiophene composite modified electrode prepared in Example 1, the oxidation peak current values were recorded respectively, and the corresponding standard curve was plotted. The results are shown in FIG. Figure 4 As shown. Figure 4 As can be seen from A, the detection potential of CIP is about -0.06V. In the range of 0.015 to 1.5 μmol / L, the fitting regression equation of ciprofloxacin concentration and DPV oxidation peak current is: pa (mA) = 0.0634C +0.211 (n=3, R 2 = 0.993), in the concentration range of 1.5 ~ 6 μmol / L, the fitting regression equation of ciprofloxacin concentration and DPV oxidation peak current is: I pa (mA) = 0.0166C + 0.281 (n=3, R 2 = 0.978), the detection limit was 85 nmol / L, and the sensitivity was 0.075 μA / μmol / L cm 2 ( Figure 4 B). The experimental results show that the zinc oxide / graphene oxide / polythiophene-based electrochemical sensor provided by the present invention can be successfully applied to the quantitative detection of ciprofloxacin, and can detect ciprofloxacin at low concentrations, with a low detection limit and good anti-interference ability. Example 6
[0023] In order to evaluate the applicability of ZnO / GO / PTH / GCE electrochemical sensor in practical applications, CIP residues in different environmental waters were detected. Based on several local water systems, water samples were taken from Wangjiahe, Nanhu Lake and Dongting Lake in Yueyang City, Hunan Province. After filtering, the collected water samples were diluted 10 times with PBS buffer (pH 7.0) for determination. In addition, the recovery rate of CIP was investigated by the standard addition method to evaluate the accuracy of the CIP detection method based on ZnO / GO / PTH ternary nanocomposite modified electrode proposed in this patent. The results are shown in Table 1.
[0024] Table 1. CIP content in actual samples detected by ZnO / GO / PTH modified electrode
[0025] This method was applied to the determination of antibiotic CIP residues in environmental water samples. The recovery rate in the sample spike recovery test could reach 90.3%~102.5%, and the results were quite satisfactory.
[0026] The above implementation modes are not limitations of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the scope of the technical solution of the present invention also belong to the protection scope of the present invention.
Claims
1. Preparation of electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite, characterized in that: The preparation method comprises the following steps: (1) Preparation of nano zinc oxide (ZnO): prepare a certain concentration of zinc acetate dihydrate aqueous solution, add a certain concentration of sodium hydroxide solution until the solution is alkaline, and continue to stir the reaction. Wash the precipitated product with deionized water for several times, freeze-dry it, place it in a muffle furnace for calcination for several hours, grind the obtained solid mortar to obtain nano zinc oxide particles. (2) Preparation of zinc oxide / graphene oxide / polythiophene (ZnO / GO / PTH) ternary nanocomposite material: first take a certain amount of nano zinc oxide particles prepared in step (1), use anhydrous ethanol as a solvent, prepare a uniformly dispersed suspension, add an appropriate amount of graphene oxide, and react with ultrasound for a certain time. Prepare polythiophene (PTH) by chemical oxidation polymerization, take a certain amount of the prepared PTH and add it to the above reaction solution, and continue to ultrasound. After the reaction is completed, filter the obtained solid, wash and dry it, and obtain the zinc oxide / graphene oxide / polythiophene ternary nanocomposite material. (3) Preparation of zinc oxide / graphene oxide / polythiophene ternary nanocomposite modified electrode (ZnO / GO / PTH / GCE): A proper amount of zinc oxide / graphene oxide / polythiophene dispersion was drop-coated on the surface of pretreated glassy carbon electrode (GCE) by drop coating method and allowed to dry naturally to obtain zinc oxide / graphene oxide / polythiophene ternary nanocomposite modified electrode ZnO / GO / PTH / GCE.
2. The preparation of the electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite according to claim 1, characterized in that: In the step (1), the concentration of zinc acetate dihydrate is 0.1 mol / L, the volume is 100 mL, the concentration of sodium hydroxide is 0.5 mol / L, the pH is 8.0, the stirring reaction time is 2 h, the freeze drying time is 12 h, and the pyrolysis reaction conditions in the muffle furnace are calcined at 400° C. for 2 h.
3. The preparation of the electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite according to claim 1, characterized in that: In the step (2), the amount of nano zinc oxide, graphene oxide and polythiophene is 20 mg, the ultrasonic dispersion time of nano zinc oxide particles is 1 h, graphene oxide and polythiophene are added in sequence, the ultrasonic time interval is 0.5 h, and the drying condition is: vacuum drying at 80 ° C for 12 h.
4. The preparation of the electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite according to claim 1, characterized in that: In the step (3), the volume of the zinc oxide / graphene oxide / polythiophene ternary nanocomposite dispersion is 8 μL, the concentration is 0.2 mg / mL; the volume fraction of acetic acid is 10%, and the amount of chitosan is 0.05 g.
5. An application of an electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite prepared by claim 1, characterized in that: The electrochemical sensor is successfully applied to the detection of ciprofloxacin (CIP) content in water.
6. The application method of the electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite as described in claim 5, characterized in that: The detection method mainly comprises the following steps: Ⅰ. Prepare 1.2 mmol / L ciprofloxacin standard solution and environmental water sample solution; Ⅱ. Using the prepared zinc oxide / graphene oxide / polythiophene ternary nanocomposite modified electrode as the working electrode, platinum sheet as the counter electrode, and silver / silver chloride as the reference electrode, cyclic voltammetry, differential voltammetry and electrochemical impedance spectroscopy were used to study the electrochemical behavior of ciprofloxacin (CIP) on the modified electrode ZnO / GO / PTH / GCE. Ⅲ. Different concentrations of ciprofloxacin solutions were detected by differential pulse voltammetry, and the relationship between the oxidation peak current value and its concentration was recorded and a standard curve was established. Environmental water samples were determined by the standard addition method and the recovery rate was calculated.
7. The application method of the electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite according to claim 5, characterized in that: The sample solution in step I is prepared by diluting the actual water sample with a PBS buffer solution of pH=7.0 at a ratio of 1:10 for later use.
8. The application method of the electrochemical sensor based on zinc oxide / graphene oxide / polythiophene ternary nanocomposite according to claim 5, characterized in that: The CV scan rate was 50 mV / s; the DPV amplitude was 0.05 V, and the potential increment was 0.004 V; the initial frequency Init E(V) of EIS was -0.23 V, the amplitude was 0.005 V, and the rest time was 2 s.